Flood estimation at ungauged river basins in Sarawak by regionalisation technique - Onni Suhaiza, Binti Selaman (Universiti Malaysia Sarawak, UNIMAS, 2007)
This study is about flood estimation at ungauged basin in Sarawak by utilizing the regionalization technique. There are 21 major river basins in Sarawak. Being the largest state in Malaysia and still not fully developed, Sarawak has only about 60 gauging stations distributed throughout the state. However, due to limited records and tidal influence, discharges records from only 19 stations could be used in this study.